Alkaloid-driven multi-target synergy of Tripterygium wilfordii polyglycosides overcomes cisplatin resistance in ovarian cancer by coordinated inhibition of PTPN11/EGFR/JAK signaling - Lin, Bing; Zhang, Minxin; Wang, Ying (Frontiers in Pharmacology, 2025)
ObjectiveTripterygium wilfordii polyglycoside (TWP) is a standardized extract from T. wilfordii Hook. f. and an oral prescription drug approved by the China Food and Drug Administration (now NMPA) for clinical use in inflammatory and autoimmune diseases. Leveraging its existing clinical approval, elucidating its anti-tumor mechanisms has high translational value for expanding its indications into oncology. This study aimed to clarify whether TWP can overcome cisplatin resistance in ovarian cancer and to explore a mechanism potentially centered on its alkaloid constituents through an integrated “prediction–validation” strategy.MethodsUPLC-QTOF-MS was used for chemical profiling. Network pharmacology predicted putative targets, validated by GEO transcriptomic datasets. Key alkaloid–target interactions were examined by molecular docking and 100-ns MD simulations. In vitro assays (CCK-8, Annexin V-FITC/PI, Western blot) in cisplatin-resistant A2780/DDP cells confirmed phenotypic and mechanistic effects.ResultsThirty-eight constituents were identified, including 18 alkaloids. Five core targets (EGFR, JAK1, JAK2, PTPN11, SRD5A1) were pinpointed by network–clinical integration. Several alkaloids ranked among the top compounds by network degree, exhibited strong predicted binding affinities (ΔG ≤ −7 kcal/mol), and formed stable complexes in molecular dynamics simulations. Functionally, TWP reduced viability, induced apoptosis, and de-phosphorylated EGFR, JAK1/2, and PTPN11, downregulated SRD5A1, and suppressed PI3K-AKT, JAK-STAT, and ERK-MAPK signaling.ConclusionOur findings suggest that alkaloids in TWP may exert multi-target synergy to disrupt key survival pathways driving cisplatin resistance in ovarian cancer. These mechanistic insights not only rationalize its observed anti-tumor activity but also support its potential clinical repurposing from an approved anti-inflammatory drug to an oncology therapeutic.